Proximal aortic compliance in young male endurance athletes: An MRI study - Tarumi, T.; Yamabe, T.; Fukuie, M.; Kimura, R.; Zhu, D. C.; Ohyama-Byun, K.; Maeda, S.; Sugawara, J. (Medicine & Science in Sports & Exercise, 2021)
Introduction: High-intensity endurance training can elicit profound cardiac adaptations; however, the current evidence as to its impact on the proximal aorta is limited. The purpose of this study was to investigate the morphological and functional characteristics of the proximal aorta in endurance athletes. Methods: Fifteen young male middle- and long-distance runners were compared with 19 age- and sex-matched sedentary control participants. CINE phase-contrast magnetic resonance imaging was used to measure blood flow velocities and cross-sectional areas of the ascending and proximal descending aorta. Aortic blood pressure was measured simultaneously during the phase-contrast magnetic resonance imaging scan using a generalized transfer function. Maximal oxygen uptake (V.O2max) was measured in the athletes. Left ventricular morphology was assessed in a subgroup of participants (n = 16) with cardiac magnetic resonance imaging. Results : The athlete group exhibited an average V.O2max of 69.5 ± 3.1 mL/kg·min, which is above the 90th percentile of men with similar age according to the American College of Sports Medicine guideline. The athletes had significantly higher stroke volume and slower heart rate at rest and greater left ventricular end-diastolic volume and mass than the sedentary participants. Significantly larger cross-sectional areas and higher compliance of the ascending and proximal descending aorta were also found in the athletes, independently of body surface area. Moreover, higher compliance of the ascending aorta was associated with greater stroke volume (r = 0.382, P = 0.026) and slower heart rate (r = -0.442, P = 0.009) across all participants. Conclusions: The proximal aorta of young male endurance athletes undergoes morphological and functional adaptations that may be resulting from the significant hemodynamic alterations associated with their cardiac function.